Gestalt modeling of international tourism behavior: Applying dimensional qualitative research in constructing grounded theory - Martin, D.; Woodside, Arch (John Wiley & Sons, Inc., 2011)
Conventional, dominant logic research methods include collecting and analyzing data to test hypotheses in a deductive theory using empirical positivistic methods. In contrast, grounded theory (i.e., building and revising propositional statements of relationships from questioning and observing informants in specific use contexts) constructs theory from data (Glaser & Strauss, 1967). This article demonstrates the application of McCracken's (1988) long interview method to collect data for grounded theory construction. Both emic (self) and etic (researcher) interpretations of international visitor experiences focus on making sense of leisure travel thinking processes (including unconscious/conscious beliefs, attitudes, and choices) and tourist behavior. In this article, long interviews of Japanese tourists visiting Hawaii's Big Island enable mapping and comparing visitors' plans, motivations, choices, and consequences. The results demonstrate nuanced complexities of visitors' travel-related unconscious/ conscious thinking and behavior. Also, the findings uncover the emergence of a possible segment of visitors—the kyooiku tsuaa (education touring) segment for the State of Hawaii's largest island (i.e., Hawaii, also known as the Big Island).